A pilot study – acute exposure to a lowintensity, low-frequency oscillating magnetic field: effects on carrageenan-induced paw edema in mice - Yoshimura, Tania M.; Meneguzzo, Daiane T.; Lopes-Martins, Rodrigo A. B. (Revista Brasileira de Física Médica, 2015)
The purpose of this paper was to evaluate the effects of an oscillating magnetic field (MF) on edema evolution in an animal model. Paw edema was induced in 32 female Swiss mice by injecting 50 µL of 1.0% carrageenan, diluted in saline solution in the left hind footpad. Animals were randomly assigned into four Experimental (exposed to different field frequencies) and two Control Groups. Groups 1 (0 Hz), 2 (3 Hz), 3 (9 Hz) and 4 (15 Hz) were exposed for 60 seconds to an oscillating MF (300 mT) in the first, second, and third hour after the injection. Control Groups (CGN and DCL) were not exposed to the MF and diclofenac was administered to DCL Group one hour after the edema induction. Paw volumes were determined every hour using a water plethysmometer. The results were graphed against time and, to evaluate the edema, the area under the curve (AUC) was measured. All groups receiving some form of intervention (1, 2, 3, 4 and DCL) revealed AUC values that were substantially lower than those of the CGN Group. DCL had the lowest reduction percentage (25.0±6.1%) and Group 3, the highest (46.9±4.0%). Compared to the results of DCL, only Groups 2 and 3 showed significantly lower AUC values. Also, with statistical relevance, Group 3 showed lower AUC values than Groups 1 and 4. According to this experiment, acute exposure to oscillating MF yields positive results in the regression of carrageenan-induced edema in mice, with indications that such effect depends on the field frequency